The Role of Rock Phosphate and Farm Yard Manure Combined-Phosphate-Solubilizing Bacteria in Increasing Nutrient Uptake and Soybean Yield - Aidi Noor (Jurnal Ilmu Tanah dan Lingkungan, 2005)
The aims of the experiment were to evaluate the effect of rock phosphate application and combination betweenphosphate-solubilizing bacteria with farm yard manure on nutrient uptake and yield of soybean. Factorial experiment design with two factors was used in randomized complzte block design with three replications. The first factors was level of rockphosphate i.e. : 0; 30; 60; 90 kg P ha· I, and the second factor was combination of phosphate solubili=ing bacteria andfarm yard manure: without phosphate solubi/i=ing bacteria andfarm yard manure; phosphate solubilbing bacteria (Pseudomonas fluorescens); farm yard manure 10 ton ha"I, and phosphate solubilizing bacteria + farm yard manure. The results indicated that rock phosphate and combination of phosphate solubilizing bacteria andfarm yard manure application increased nutrient (N, p, K) uptake and grain yield of soybean. Optimum dosage of rock phosphate in soil without phosphate-solubilizing bacteria andfarm yard manure (control) was 72.15 kg P hdl which gave maximum yield of soybean was 7.73 g pori. While with phosphate-solubilizing bacteria. farm yard manure and phosphate solubilizing bacteria+farm yard manure obtained optimum dosage of rock phosphate were 62.26, 63.94, and 62. 21 kg P hd1 , respectively, which gave maximum yield of soybean were 8.17, 7.95, and 8.43 g pori, respectively.